The Implementation of E-Court at the Banten High Religious Court: Challenges, Barriers, and Prospects within Indonesia’s Legal System - Yasmita, Yasmita; Fathonih, Ah.; Saepulah, Usep; Burhanuddin, Burhanuddin; Ridwan, Mohammad; Saputra, Edy (Hukum Keluarga Islam IAIN LANGSA, 2025)
The main problems in the implementation of the e-Court system in the Religious Court are the limited information technology infrastructure, technical constraints, and low digital literacy of the parties to the case. This condition creates a gap between the goal of digitizing the judiciary and the reality of implementation in the field. This study aims to examine the implementation of the Supreme Court of the Republic of Indonesia Regulation Number 7 of 2022 concerning the administration of cases and electronic trials at the Religious Court under the jurisdiction of the Banten High Court of Religion. The method used is juridical-empirical with a qualitative approach, through data collection in the form of in-depth interviews and direct observation at six Religious Courts in the jurisdiction. The results of the study show that e-Court is able to improve the efficiency of administration and trial processes, but still faces obstacles in the form of limited infrastructure, lack of digital literacy of the parties, and lack of ongoing technical support. The contribution of this research lies in providing comprehensive strategy recommendations through strengthening infrastructure, increasing user capacity, and policy socialization so that the implementation of e-Court can be more equitable, effective, and support the realization of a fast, transparent, and fair judicial system.